Dinamika Insurgensi Dalam Konflik Horizontal Di Papua Melalui Pola Gerakan Dan Respons Negara - Anugrah, Muhammad Lutfi; Timur, Fauzia G. Cempaka; Utomo, Bambang (Syntax Literate, 2026)
The horizontal conflict in Papua remains one of the most complex and enduring conflicts in Indonesia, involving the interaction of historical grievances, identity politics, security responses, and struggles over legitimacy. Previous studies have tended to examine Papuan conflict in partial ways, such as armed resistance, securitization, media representation, or humanitarian issues, leaving limited analysis that integrates insurgent movement patterns and state responses within a single asymmetric warfare framework. This study aims to analyze the dynamics of insurgency in Papua by examining the patterns of insurgent movements and the state’s responses in the context of horizontal conflict. The research employed a qualitative case study approach, using in-depth interviews, documentation, and literature review as data collection techniques. The findings show that the Papuan conflict reflects the characteristics of asymmetric conflict, marked by unequal power relations between the state and non-state actors. Insurgent movements have shifted from predominantly territorial armed resistance to multi-arena strategies operating in political, international, and digital spaces. At the same time, state responses remain dominated by security approaches, although they are also accompanied by development, administrative governance, and narrative management. The study concludes that the persistence of conflict in Papua is shaped by the relational interaction between insurgent adaptation and state response. Therefore, conflict management requires a more integrative, adaptive, and context-sensitive approach that goes beyond a purely territorial and coercive logic.